Experimental and modeling assessment of CO2 EOR and storage performances in tight oil reservoir, Yanchang oilfield, China - Hong Yang; Heng Wang; Xiangzeng Wang; Yuchen Xin; Lijun He; Zunsheng Jiao; Jie Zou (Journal of CO2 Utilization)
Previous experimental studies have shown that CO2 injections can significantly enhance oil recovery in tight oil reservoirs and sequestrate CO2 permanently. However, performance varies in places when the technologies are scaled up in field pilot tests. Therefore, investigating CO2 EOR (Enhanced Oil Recovery) and storage mechanisms during CO2 injection in field-scale tight sandstone reservoirs is crucial. In this study, laboratory Pressure-Volume-Texperature (PVT) tests and field pilot tests of CO2 injection in a tight oil reservoir of the Yanchang oilfield in the Ordos Basin were analyzed. Reservoir simulations of CO2 injections, including continuous and water alternative gas injections, are conducted after history matching. Laboratory PVT results show that oil viscosity decreases from 5.10 to 2.38 mPa·s as pressure reduces from initial formation conditions to atmospheric pressure, and swells oil to 1.50 times at a saturation pressure of 240.0 bar, which is larger than the minimum miscible pressure of 178.0 bar from the slim tube test. Reservoir simulation results of continuous and WAG injection scenarios show that oil production increases with CO2 injection rate, and oil recovery increments are 21.6 % and 19.3 %, respectively, for Case 3 and Case 5. This is because reservoir pressure increases with more injected CO2, resulting in higher displacement efficiency, and larger amounts of CO2 can also lead to higher sweep efficiency in the lateral directions. However, CO2 EOR efficiency decreases gradually after the CO2 breakthrough. In addition, CO2 migration in the lateral direction relates to the CO2 injection rate. The areas of dissolved CO2 are larger than those of gaseous CO2, especially for WAG cases, while both increase with CO2 injection rate due to a larger pressure gradient. The amount of CO2 through structural trapping for the continuous injection cases is higher than solubility trapping, followed by residual trapping. Differently, the amounts of gaseous CO2 are close to those of the dissolved CO2 for the WAG cases due to water injection. The findings in this study are significant for understanding and demonstrating the CO2 EOR, storage mechanisms in lab and field scales, and provide a valuable reference for scaling up the technologies in tight oil reservoirs.